Rootstocks and potassium fertilization on yield performance and quality of ‘Niagara Rosada' grapevine under subtropical conditions - Callili, Daniel [UNESP]; Silva, Marlon Jocimar Rodrigues da [UNESP]; Sánchez, Camilo André Pereira Contreras [UNESP]; Basílio, Letícia Silva Pereira [UNESP]; Macedo, Bruno Marcos De Paula [UNESP]; Teixeira, Luiz Antonio Junqueira; Lima, Giuseppina Pace Pereira [UNESP]; Tecchio, Marco Antonio [UNESP] (Southern Cross Publishing, 2022)
The current study aimed to assess the influence of rootstocks (‘IAC 572' and ‘IAC 766') and potassium fertilization with different sources (KCl and K2SO4) and concentrations (0, 75, 150 and 300 kg ha-1 K2O) regarding to yield performance and grape quality of ‘Niagara Rosada', as well as the variation of K availability in soil. Thus, yield components; physical characteristics of bunches and berries; chemical composition, bioactive compounds, and antioxidant activity of grape berry; leaf K content; and variation of K availability in soil were evaluated in two consecutive seasons (2017 and 2018). Results showed no influence of rootstocks on yield performance of ‘Niagara Rosada'; however, grapevines grafted on to ‘IAC 766' produced berries with higher concentration of total flavonoids and anthocyanins. Furthermore, KCl provided higher concentration of total flavonoids and anthocyanins compared to K2SO4. In general, potassium sources had similar effects on the variation of K availability in soil. Results indicated that there was small effect between K doses with regards to production and qualitative parameters. We therefore estimated a fertilization rate of 150 kg ha-1 K2O to maintain K concentration in soil after each production cycle.
Keywords: antioxidant compounds; grafting; K replacement; physicochemical characteristics; table grapes